Pengaruh Aktiva Tetap Dan Ekuitas Terhadap Laba Bersih Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2024 - Puspita, Bunga Ayu; Pormes, Cindy Laura; Farida, Farrah; Apriasti, Inayah (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2025)
This study examines the impact of fixed assets and equity on the net income of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2024. The study employs a correlational design utilizing secondary data derived from the financial statements of 15 selected firms. The data were analyzed using multiple linear regression with IBM SPSS Statistics 27, incorporating classical assumption tests including normality, multicollinearity, and heteroscedasticity. The findings indicate that both fixed assets and equity, individually and jointly, exert a positive yet statistically insignificant influence on net income. The F-test reveals no significant joint effect of the independent variables on net income, while the T-tests suggest that neither fixed assets nor equity individually have a substantial impact on net profitability. The coefficient of determination (R ²) indicates that only 24,1% of the variance in net income is explained by the two independent variables, with the remaining 75,9% attributed to external factors. These results imply that other financial components may have a more pronounced influence on profitability whitin the manufacturing sector.